(untitled) (Altre Modernità, 2014)
This autobiographical novel is analyzed as a novel typical of the second-generation of mizrahi writers , characterized by a particular relationship, marked by close ties with the tradition - represented by the generation of mothers and fathers and grandmothers and grandfathers - and with memory and that differentiates them from ashkenazim. These narratives leave a lot of space to autobiography and fill the silence that has occurred in the post-migration period, similarities that can also be found among the Jewish writers of the second generation originating from Algeria and emograted to France.